Theological Analysis and Biblical Perspective on LGBTQ+ Affirmation in the Indonesian Church - Garry Robert M. Tengker (Eduvest - Journal of Universal Studies, 2026)
This research aims to provide a theological and biblical analysis of the demand for LGBTQ+ affirmation within Indonesian churches. The research method applied is normative theological research based on a literature review, using exegesis, exposition, comparative analysis, as well as deductive and inductive synthesis. The findings indicate that Indonesian churches consistently reject LGBTQ+ affirmation as being contrary to the authority of Scripture, while still emphasizing the love of Christ in pastoral ministry. The study also reveals that academic discourse on LGBTQ+ affirmation in Indonesia remains limited; however, the presence of LGBTQ+ members in congregations is real and creates urgent pastoral needs. Variations in pastoral approaches across denominations demonstrate efforts to balance love and truth. The findings imply that the church must practice non-discriminatory love while firmly rejecting the normalization of practices that contradict biblical truth, and that Indonesian churches need to develop contextual theological responses and pastoral strategies that address the growing exposure of younger generations to global affirmation discourse. This study concludes that the appropriate way for the church is to practice non-discriminatory love while firmly rejecting the normalization of practices that contradict biblical truth.